Vaginal surgery - Bedoya Hevia, Mariano (2015)
In recent years Gynecological Surgery Vaginal, has taken a leading position in many schools, compared with surgery through the abdomen. These developments are evident for vaginal route celiotómica as indications, contra-indications and techniques to follow for the treatment of conditions of the external organs, vagina and neck, it is common to be well known.